Rooting embodied wisdom for Black futures - Orlando Zane Hunter Jr.; Ricarrdo Valentine; Mary Rodriguez (Urban Food Systems Symposium, 2022)
Over the last 10 years, there has been a resurgence in urban agriculture in an effort for Black communities to reclaim autonomy over food sources and diets and a way to empower them to engage once again in the agricultural industry. This reconnecting builds collective agency and community resilience (CACR) (White, 2019). The benefits of urban agriculture within Black communities bring spiritual, mental, and physical wellness to the forefront, empowering upward mobility and encouraging an autonomous revenue structure. This research looks to the pioneers of the community supported agriculture (CSA) movement as a rooted framework for self- sufficiency, communal resilience, and land sovereignty (Baszile, 2021). Art is a way of documenting and connecting individuals with specific subject matter that yields transformative understanding. Specifically, movement is a unique language spoken through the body and can tell stories about the lives and experiences of a person. Food is transportive, movement-based, creative expression that has been shown to improve health outcomes and to expand consciousness, promote healing, and self-awareness (Stuckey & Nobel, 2010). We see movement as an opportunity to engage Black urban growers in self-empowered healing in connection with the environment around them to surpass historical trauma. This qualitative study used narrative inquiry methodology to explore the ideas of Black growers’ relationship to land, growing fresh food, and how those relationships to the earth influence how Black communities can secure and ensure future growth. Through an innovative participatory interview, we solicited stories from nine urban farmers incorporating elements of movement ranging from the grower’s contemporary movement and African diasporic agricultural dances that lend to storytelling. Three emergent themes from one-on-one interviews with Black growers emerged: (1) the generational gap to sustain and transfer agricultural wisdom; (2) reengagement with the earth is vital for Black communities for holistic health and wellbeing; and (3) longevity of urban agriculture persists to be a concern for elder stewards of the earth due to ever changing urban land conditions. This research illustrates a historical narrative of resilience that exists within Black communities’ relationship to the earth. These stories are sacred and important to share because Black communities are so often regulated to urban areas and stigmatized due to lack of access to resources and consistently meet structural oppressive forces. As a Black movement artist and grower, I see movement as an expressive way to connect and highlight the dimensionality of the food justice movement.
Keywords: urban agriculture; narrative inquiry; resilience; Black growers